On Sacrifice - Halbertal, Moshe (Princeton : Princeton University Press, 2012)
The idea and practice of sacrifice play a profound role in religion, ethics, and politics. In this brief book, philosopher Moshe Halbertal explores the meaning and implications of sacrifice, developing a theory of sacrifice as an offering and examining the relationship between sacrifice, ritual, violence, and love. On Sacrifice also looks at the place of self-sacrifice within ethical life and at the complex role of sacrifice as both a noble and destructive political ideal. In the religious domain, Halbertal argues, sacrifice is an offering, a gift given in the context of a hierarchical rela
Description based upon print version of record.
Keywords: Sacrifice; Self-sacrifice.; Sacrifice; Self-sacrifice.; RELIGION / Reference; Electronic books